Influence of Customer Value, Customer Preferences, and Perceived Product Quality on Repurchase Decision for Kopi Tembalang Signature Coffee Products - Taviyastuti; Najla Debi Habsari; Yusmar Ardhi Hidayat (Admisi dan Bisnis, 2026)
Coffee is one of the most popular beverages among Indonesians and has become part of their daily lifestyle. The growth of the modern coffee industry has accelerated, marked by the proliferation of coffee shops in various regions. One such coffee shop is Kopi Tembalang, which has a flagship product called Signature coffee. However, sales of Signature coffee have declined throughout 2024. This condition indicates the possibility of problems with factors that affect customer loyalty, particularly those related to repeat purchase decisions. The purpose of this study is to examine how customer value, customer preferences, and perceptions of product quality affect decisions to repurchase Signature coffee products from Kopi Tembalang. Eighty respondents were given a questionnaire as part of the quantitative research methodology. To ascertain the impact of independent variables on repurchase decisions, the data was subjected to multiple linear regression analysis using SPSS software. The findings indicate that repurchase decisions (Y) are not significantly impacted by customer value (X1). On the other hand, it has been demonstrated that repurchase decisions (Y) are positively and significantly impacted by customer preferences (X2) and perceptions of product quality (X3). This demonstrates that consumer preferences and opinions of high-quality products have a greater impact on repurchases than do opinions of customer value.